Successful reversal of neuropathic eye pain by treatment of occult ocular surface disease: Case series and implications - Steven L. Maskin (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To report the successful approach to managing neuropathic dry eye-like pain (NP) in three consecutive patients described as severe: 1) “burning fire,” “burning acid,” and “horrible burning pain” with hyperalgesia and allodynia, 2) refractory to topical anesthetic (TA), and 3) without surface hyperemia nor vital staining. Observations: Two of three patients' pain was reversed with significant symptom relief within 48 hours by identification of occult obstructive Meibomian gland dysfunction (o-MGD) and treatment using Meibomian gland probing (MGP) with intraductal steroid lavage (MGP(s)) and aqueous tear deficiency (ATD) treated with punctal thermocautery (PO). The third patient's pain was reversed within one week after treatment of superior conjunctivochalasis (CCh) using amniotic membrane surface reconstruction and ATD using PO with subsequent MGP and MGP(s) for o-MGD. Conclusions and importance: It has been generally thought that central (NP) is strongly suggested by triad of 1) severe chronic burning pain with hyperalgesia and allodynia, 2) refractory to TA with 3) minimal signs. In this three-case series, treatment of occult surface disease consistently led to symptom reversal. Results may represent salutary effect of successful treatment to suppress nociceptive inflammation leading to reversal of central NP. Alternatively, the current triad of diagnostic criteria may be unable to differentiate centralized NP from peripheral sensitization alone, thereby requiring rigorous examination to uncover occult, yet treatable, surface disease to restore eye comfort and reverse psychosocial sequelae when possible. Furthermore, rigorous targeting of surface disease in patients with this pain triad may obviate unnecessary systemic treatments with associated risks of serious side effects.